2008
DOI: 10.1029/2007jd008762
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Aura Microwave Limb Sounder ClO measurements

Abstract: [1] We assess the quality of the version 2.2 (v2.2) ClO measurements from the Microwave Limb Sounder (MLS) on the Earth Observing System Aura satellite. The MLS v2.2 ClO data are scientifically useful over the range 100 to 1 hPa, with a single-profile precision of $0.1 ppbv throughout most of the vertical domain. Vertical resolution is $3-4 km. Comparisons with climatology and correlative measurements from a variety of different platforms indicate that both the amplitude and the altitude of the peak in the ClO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 33 publications
6
124
0
Order By: Relevance
“…The version 2.2 ClO measurements were validated in Santee et al (2008). Here, we use the v4.2 retrievals (Livesey The times for these measurements remain consistent within ±4 min throughout the entire Aura mission.…”
Section: Clo Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The version 2.2 ClO measurements were validated in Santee et al (2008). Here, we use the v4.2 retrievals (Livesey The times for these measurements remain consistent within ±4 min throughout the entire Aura mission.…”
Section: Clo Measurementsmentioning
confidence: 99%
“…The loweraltitude ClO continues to show a gradual increase until midSeptember and then experiences a sharp decline, as it converts back to the reservoir gases. Santee et al (2008) present a detailed study of the seasonal evolution of the partitioning between ClO, HCl (from MLS), and ClONO 2 (from the Atmospheric Chemistry Experiment Fourier Transform Spectrometer; ACE-FTS) in the Arctic and Antarctic. Figure 3 shows measurements of day minus night ClO column from ChlOE during 2006 together with those from the coincident (within ±2 • latitude and ±15 • longitude of Scott Base) MLS measurements.…”
Section: Clo Measurementsmentioning
confidence: 99%
“…The time resolution of the measurements is about 3500 profiles per day. The estimated uncertainty of typical ozone and ClO retrievals is about 5-10 and 10-20 %, respectively (Livesey et al, 2013;Santee et al, 2008a;Froidevaux et al, 2008). For a comparison with the measurements, the model results (6 h output) are interpolated to the measurement locations.…”
Section: Simulations and Measurementsmentioning
confidence: 99%
“…Large variability in Antarctic ozone loss has been seen in the last few years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) relative to other winters since 1992 (e.g., Tilmes et al, 2006;Huck et al, 2007;Yang et al, 2006;Santee et al, 2008a). For instance, the winters of 2004, 2010, and 2012 were relatively warm, with minor warmings and, hence, limited ozone loss (Santee et al, 2005;de Laat and van Weele, 2011;WMO, 2014).…”
mentioning
confidence: 99%
“…In Belgrano it is about 200 h, while at SPS it is 668 h. Greater rates of accumulated light could lead to activation of more halogen compounds at SPS. Santee et al (2008) found a positive chlorine gradient toward the pole for this season by analysing AURA-MLS data. Therefore, more activated chlorine at SPS could be responsible of the higher ozone loss rate.…”
Section: Ozone Distribution Within the Vortex: Belgrano Vs South Polementioning
confidence: 81%